2009
DOI: 10.1007/s10499-009-9254-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of natural olive oil antioxidants utilization in rainbow trout (Onchorynchus mykiss) feeding

Abstract: Olive mill vegetation water (VW) is an olive oil by-product rich in polyphenols has powerful antioxidant effects. In light of the interest on the research of novel natural antioxidants to use in fish feed, the aim of this research was to use VW as a potential substitute for artificial antioxidants in rainbow trout diet as well as checking its effects on the blood chemistry and digestive organ physiology of the fish. The experimental plan was monofactorial, balanced (4 9 3) and the experimental factor considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…It is also evident that the antioxidant effect of VW inclusion in fish feed increased with increasing VW level. In the study on rainbow trout nutrition with VW inclusion by Sicuro et al (2009), similar results were obtained in the TBARS analysis: there was an improvement in the TBARS analysis in fish consuming VW-supplemented feed inclusion, but the difference was not evident in all of the samples analysed. We also investigated several physiological parameters to determine whether certain polyphenols had negative effects.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is also evident that the antioxidant effect of VW inclusion in fish feed increased with increasing VW level. In the study on rainbow trout nutrition with VW inclusion by Sicuro et al (2009), similar results were obtained in the TBARS analysis: there was an improvement in the TBARS analysis in fish consuming VW-supplemented feed inclusion, but the difference was not evident in all of the samples analysed. We also investigated several physiological parameters to determine whether certain polyphenols had negative effects.…”
Section: Discussionsupporting
confidence: 65%
“…The absence of differences in the production traits between experimental treatments suggests the possibility of utilising VW in sea bream feed. Sicuro et al (2009) reported a number of anti-nutritional effects of VW in a study involving the inclusion of similar levels of VW in rainbow trout feed. Sea bream seems to be more tolerant to high levels of these polyphenols in fish feed, and this could be an advantage for the future of the aqua-feed industry, given the large production of VW in Mediterranean countries, despite the need for a polyphenol purification method.…”
Section: Discussionmentioning
confidence: 99%
“…Hematic cortisol is a parameter commonly used to evaluate fish welfare (Sadler et al, 2000;Campbell, 2004;Haukenes et al, 2008;Sicuro et al, 2009) and provides a good indication of intensity and duration of stress in gilthead seabream (Jentoft et al, 2005;Syriou et al, 2011). Our result clearly suggests that PBM meal based diet did not determine, per se, stress in this fish species.…”
Section: Fish Welfarementioning
confidence: 99%
“…Additionally, the diversification of new protein ingredients (from animals and plants), and identification of additives (natural or synthetic) with “intestinal protective” activity to promote growth and health have been made a priority (Refstie et al, 2010; Sicuro et al, 2010; Czubinski et al, 2014). Thus, the effects of nutrition on genomics and immunity are being addressed (Montero et al, 2010; Hernández et al, 2013).…”
Section: Aquaculture Nutrition: Trends and Future Perspectivementioning
confidence: 99%